Structural insights into i-motif DNA structures in sequences from the insulin-linked polymorphic region - Guneri, Dilek; Alexandrou, Effrosyni; El Omari, Kamel; Dvořáková, Zuzana; Chikhale, Rupesh V; Pike, Daniel T S; Waudby, Christopher A; Morris, Christopher J; Haider, Shozeb; Parkinson, Gary N; Waller, Zoë A E (Nature communications, 2024)
The insulin-linked polymorphic region is a variable number of tandem repeats region of DNA in the promoter of the insulin gene that regulates transcription of insulin. This region is known to form the alternative DNA structures, i-motifs and G-quadruplexes. Individuals have different sequence variants of tandem repeats and although previous work investigated the effects of some variants on G-quadruplex formation, there is not a clear picture of the relationship between the sequence diversity, the DNA structures formed, and the functional effects on insulin gene expression. Here we show that different sequence variants of the insulin linked polymorphic region form different DNA structures in vitro. Additionally, reporter genes in cellulo indicate that insulin expression may change depending on which DNA structures form. We report the crystal structure and dynamics of an intramolecular i-motif, which reveal sequences within the loop regions forming additional stabilising interactions that are critical to formation of stable i-motif structures. The outcomes of this work reveal the detail in formation of stable i-motif DNA structures, with potential for rational based drug design for compounds to target i-motif DNA.
Keywords: Insulin; sekvence nukleotidů; nukleotidové motivy; krystalografie rentgenová; Nucleic Acid Conformation; inzulin; tandemové repetitivní sekvence; polymorfismus genetický; reportérové geny; promotorové oblasti (genetika); G-Quadruplexes; Polymorphism, Genetic; molekulární modely; Crystallography, X-Ray; Models, Molecular; konformace nukleové kyseliny; Animals; lidé; Tandem Repeat Sequences; Humans; zvířata; Promoter Regions, Genetic; DNA; Nucleotide Motifs; G-kvadruplexy; Base Sequence; Genes, Reporter